2015
DOI: 10.1007/s10549-015-3386-3
|View full text |Cite
|
Sign up to set email alerts
|

Combined inhibition of glycolysis and AMPK induces synergistic breast cancer cell killing

Abstract: Targeting glycolysis for cancer treatment has been investigated as a therapeutic method but has not offered a feasible chemotherapeutic strategy. Our aim was to examine whether AMP-activated protein kinase (AMPK), a conditional oncogene, rescues the energetic stress and cytotoxicity induced by 2-deoxyglucose (2-DG), a glycolytic inhibitor, and the related mechanisms. Luciferin/luciferase adenosine triphosphate (ATP) determination, Western analysis, qRT-PCR analyses, MTT growth assay, clonogenic assay, and stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 37 publications
1
39
0
Order By: Relevance
“…According to a recent study, a broad spectrum of mechanisms may be responsible for the resistance of MCF-10A cells to anticancer compounds. These include differences in the subcellular localization of Bik (Trejo-Vargas et al 2015) and the KLF8/EGFR signalling pathway (Li et al 2015), differences in stearoyl-CoA desaturase-1 activity (Belkaid et al 2015) and combined inhibition by glycolysis and AMP-activated protein kinase (Wu et al 2015), and differences in mitochodrial-mediated apoptosis (Taha et al 2015). Therefore, the exact mechanism responsible for the selective activity of physodic acid in breast cancer should be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent study, a broad spectrum of mechanisms may be responsible for the resistance of MCF-10A cells to anticancer compounds. These include differences in the subcellular localization of Bik (Trejo-Vargas et al 2015) and the KLF8/EGFR signalling pathway (Li et al 2015), differences in stearoyl-CoA desaturase-1 activity (Belkaid et al 2015) and combined inhibition by glycolysis and AMP-activated protein kinase (Wu et al 2015), and differences in mitochodrial-mediated apoptosis (Taha et al 2015). Therefore, the exact mechanism responsible for the selective activity of physodic acid in breast cancer should be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study also indicates that CPT1C might be induced by the indirect action of activated AMPK in the MCF-7 breast cancer cell line [127]. This study showed that 2-deoxyglucose (2-DG), a glycolytic inhibitor, decreased ATP levels, Although AMPK emerges as the major contributor to the increase in CPT1C expression in cancer cells, other less explored mechanisms, such as epigenetic alterations by changes in DNA methylation, cannot be disregarded [128].…”
Section: Regulators Of Cpt1c Expression In Response To Metabolic Stressmentioning
confidence: 96%
“…The activation of AMPK by solamargine has never been shown in the past. Activation of AMPK were reported to be involved in the anti-tumor responses in several cancer types including prostate, suggesting the tumor suppressor role of this kinase1617183940 although conflicting observations have also been shown1920. Nevertheless, our results suggested that activation of AMPK signaling was involved in effect of solamargine in the controlling the growth of CRPC cells.…”
Section: Discussionmentioning
confidence: 51%
“…AMPK signaling also involves in growth, differentiation and progression of cancer, and has emerged as an attractive therapetic target to various types of cancer161718. However, conflicting reports about its cellular functions in cancer have been reported.…”
mentioning
confidence: 99%